Meningkatkan Kemampuan Bahasa Anak Tunarungu Melalui Metodematernal Reflektif Di Sekolah SLB C Muzdhalifah - Noviar Panggabean; Dea Nitami Br.ginting; Sutini Sutini; Asmidar Parapat; Mhd Iqbal (Departement of Mathematics Education, 2024)
Deaf children are children whose sense of hearing is damaged so they cannot perceive and receive sound stimuli through their hearing. Dysfunction of the sense of hearing in deaf children causes difficulty in acquiring language through hearing, thereby hampering the process of language development. This research discusses the benefits of using the Reflective Material Method (MMR) in deaf children. The aim of this research is to determine the language abilities of deaf children using the Reflective Material Method (MMR) at SLBC Muzdhalifah for class III children. This research uses a qualitative approach and the type of research used is descriptive research. The data collection methods used in this research are interview, observation and documentation methods. Based on the results of research conducted by researchers regarding the use of the Maternal Reflective Method (MMR) with deaf children in elementary class III at SLBC Muzdalifah, it has had many positive impacts, seen from the language and communication skills of SLBC Muzdalifah students.